Pulsed electric field-assisted extraction of Djenkol (Archidendron Pauciflorum) peel: Characterization, suppression of Intracellular ROS generation and inflammatory cytokines using LPS-activated RAW264.7 macrophage cells - Sirima Sinthusamran; Lalita Chotphrethipong; Soottawat Benjakul; Pilaiwanwadee Hutamekalin; Nidanut Champoochana; Theeraphol Senphan; Sitthipong Nalinanon (My University, 2024)
Djenkol (Archidendron Pauciflorum) peel is a source of phenolics with an antioxidative activity. Nevertheless, the high extraction efficacy of the target compounds is crucial for the isolation of such compounds. Pulsed electric field (PEF)-assisted extraction is the means that increase the efficacy of extraction via an electroporation mechanism. This research aimed to study the extraction of phenolics with antioxidative activities using the PEF and to investigate the anti-inflammation and antioxidative activities of the Djenkol peel extract (DPE) in RAW264.7 macrophage cells. The PEF at different electric field strengths (E) (4.5 and 6 kV/cm) and times (180, 360, and 540 ms) was implemented to extract the phenolic compounds. The PEF with the E level at 6 kV/cm for 540 ms provided the highest yield, the total phenolic content, and antioxidative activities, compared to other conditions (P<0.05). The dominant compounds in the DPE were the gallic acid and catechin. When the RAW264.7 cells were treated with the DPE at different levels (0.125, 0.25, 0.5, 0.75 and 1 μg/mL), the DPE at 0.125 and 0.25 μg/mL had no cytotoxicity, compared to the control (P<0.05). With adding lipopolysaccharide (LPS), the DPE-treated cells at 0.125 μg/mL showed the similar cell viability to that of the control (P<0.05). Additionally, the use of the DPE, particularly at 0.125 and 0.25 μg/mL, could reduce the TNF-α and IL-6 levels and reactive oxygen species (ROS) generation in the LPS-activated cells. Thus, the DPE could be used as a functional ingredient in food.
Keywords: Characterization; Phytochemical and Pharmacological Studies